PENGEMBANGAN EDUWISATA SEBAGAI BENTUK DUKUNGAN INCOME GENERATING DAERAH WISATA DILEM WILIS - Saparullah Saparullah; Nandang Mufti; Haidar Ali; Silvi Rahmawati Wibowo; Atika Sari Puspita Dewi; Faiq Nur Saidah; Dhea Paradita; Nasikhudin Nasikhudin; Muntholib Muntholib (Universitas Islam Malang, 2023)
Tourism village is one of the tourism concepts currently being activated and has attracted many people. Many benefits are obtained, such as increasing local government income, helping the community's economy around the tourism area, and empowering local communities for its management. One tourist attraction that has superior potential is Dilem Wilis Edutourism in Dompyong Village, Trenggalek Regency. Dilem Wilis tourist destination offers a reasonably wide natural Dutch Heritage. However, the vastness of the tourist area that is not in line with the management makes some tourist rides unable to be enjoyed as a whole. In this community service activity, efforts to develop Dilem Wilis Edutourism are carried out through several stages. The landscape 3D model was designed with sketchup software then fabricated with synthetic material of 1:300 scale. The results of this development stage are realized in a tangible form. There are the manufacture of 3D model of the landscape and the installation of LED strip lights that are useful for attracting tourists to visit because access to lighting is adequate, and the delivery of regional mapping is well conveyed through the Dilem Willis Eduwisata landscape 3D model.